Design, Implementation, and Evaluation of Physicians Empowerment Course for Evidence-Based MRI Prescription at Bushehr University of Medical Sciences in 2021 - Hedayat Salari; Atefeh Esfandiari (Shahid Sadoughi University of Medical Sciences, 2022)
Corrigendum: Design, Implementation, and Evaluation of Physicians Empowerment Course for Evidence-Based MRI Prescription at Bushehr University of Medical Sciences in 2021 Hedayat Salari 2,3, Atefeh Esfandiari 2,3 2 Department of Medical Education, Virtual University of Medical Sciences, Tehran, Iran 3 Department of Health Policy & Management, School of Medicine, Bushehr University of Medical Sciences, Bushehr, Iran In the above article, which was published in the Volume 6, Issue of 1, March 2022, affiliations of Hedayat Salari and Atefeh Esfandiari have been corrected.